Précis of The Illusion of Doubt - Schönbaumsfeld, Genia (International journal for the study of skepticism, 2021)
Abstract The Illusion of Doubt shows that radical scepticism is an illusion generated by a Cartesian picture of our evidential situation—the view that my epistemic grounds in both the ‘good’ and the ‘bad’ cases must be the same. It is this picture which issues both a standing invitation to radical scepticism and ensures that there is no way of getting out of it while agreeing to the sceptic’s terms. The sceptical problem cannot, therefore, be answered ‘directly’. Rather, the assumptions that give rise to it, need to be undermined. These include the notion that radical scepticism can be motivated by the ‘closure’ principle for knowledge, that the ‘Indistinguishability Argument’ renders the Cartesian conception compulsory, that the ‘New Evil Genius Thesis’ is coherent, and the demand for a ‘global validation’ of our epistemic practices makes sense. Once these dogmas are undermined, the path is clear for a ‘realism without empiricism’ that allows us to re-establish unmediated contact with the objects and persons in our environment which an illusion of doubt had threatened to put forever beyond our cognitive grasp.